The meshing framework ViennaMesh for finite element applications - Rudolf, Florian; Weinbub, Josef; Rupp, Karl; Selberherr, Siegfried (Journal of computational and applied mathematics, 2014)
The applicability of the meshing framework ViennaMesh for finite element simulations is investigated. Meshing tools are highly diverse, meaning that each software package offers specific properties, such as the conforming Delaunay property. The feasibility of these properties tends to be domain specific, thus restricting the general application of a meshing tool. For research purposes, it is desirable to have a rich toolset consisting of the various meshing packages in order to be able to quickly apply the various packages to the problem at hand. Different meshing tools have to be utilized to support a broader range of mesh properties. Further contributing to this problem is the lack of a common programming interface, impeding convenient switching of meshing backends. ViennaMesh tackles this challenge by providing a uniform meshing interface and reusable mesh-related tools, like CGAL, Gmsh, Netgen, and Tetgen. We depict the feasibility of our approach by discussing two applications relevant to finite element simulations, being a local mesh optimization and an adaptive mesh refinement application.